2023
DOI: 10.1007/s10911-023-09536-y
|View full text |Cite
|
Sign up to set email alerts
|

Culture Models to Investigate Mechanisms of Milk Production and Blood-Milk Barrier in Mammary Epithelial Cells: a Review and a Protocol

Abstract: Mammary epithelial cells (MECs) are the only cell type that produces milk during lactation. MECs also form less-permeable tight junctions (TJs) to prevent the leakage of milk and blood components through the paracellular pathway (blood-milk barrier). Multiple factors that include hormones, cytokines, nutrition, and temperature regulate milk production and TJ formation in MECs. Multiple intracellular signaling pathways that positively and negatively regulate milk production and TJ formation have been reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that mammary gland involution occurs in two distinct physiological phases in the absence of lactogenic hormone secretion [30,34]. Early apoptosis and the loss of TJs occurred in the first phase, and anoikis was irreversibly induced with a massive loss of mammary ECs after disruption of the basement membrane through the activation of MMPs in the second phase [35]. In contrast, the presence of hormones, such as PRL and CORT, enhanced the TJs formation and milk production by mammary ECs [36].…”
Section: A C C E P T E Dmentioning
confidence: 98%
“…Previous studies have reported that mammary gland involution occurs in two distinct physiological phases in the absence of lactogenic hormone secretion [30,34]. Early apoptosis and the loss of TJs occurred in the first phase, and anoikis was irreversibly induced with a massive loss of mammary ECs after disruption of the basement membrane through the activation of MMPs in the second phase [35]. In contrast, the presence of hormones, such as PRL and CORT, enhanced the TJs formation and milk production by mammary ECs [36].…”
Section: A C C E P T E Dmentioning
confidence: 98%
“…Milk is produced by epithelial cells of the mammary gland, which under the influence of both exogenous and endogenous factors undergo numerous physiological changes throughout lactation. Ultimately, these changes determine the intensity of milk component synthesis and, hence, milk composition [5]. Functional genomics studies based on gene network analysis revealed the complexity of molecular adaptation of the mammary gland to lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Kobayashi describes the biology and dysfunction of mammary epithelial tight junctions and provides a detailed protocol describing culture of mammary epithelial cells in a manner that is compatible with milk production. This article also touches upon some of the challenges that may be encountered when working with non-traditional species, such as the fact that the optimal culture conditions for mammary epithelial cells may be species-specific [ 14 ].…”
mentioning
confidence: 99%